2014
DOI: 10.1186/1471-2288-14-52
|View full text |Cite
|
Sign up to set email alerts
|

Collection of patient-reported outcomes; - text messages on mobile phones provide valid scores and high response rates

Abstract: BackgroundPatients with inflammatory rheumatic diseases have expressed a need for more frequent measurement of relevant outcomes, due to the variations in their symptoms during the day and from day to day. At present, patient-reported outcomes are extensively collected with questionnaires completed with pen and paper. However, as a measurement tool in frequent data collection the questionnaires are impractical. In contrast, text messages on mobile phones are suitable for frequent data collection.The aim of thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
31
1

Year Published

2014
2014
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 17 publications
1
31
1
Order By: Relevance
“…16 In a systematic review of survey response rates, email delivery was associated with response rates of 15%, 17 similar to the 14% response rate for CG-CAHPS delivered by email. 16 SMS administration has associated response rates ranging from 49% to 98%, [18][19][20][21] and data quality comparable to that collected by person-led phone interviews or IVR. 21 The cost of PREM administration has significant implications, yet receives little attention.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
“…16 In a systematic review of survey response rates, email delivery was associated with response rates of 15%, 17 similar to the 14% response rate for CG-CAHPS delivered by email. 16 SMS administration has associated response rates ranging from 49% to 98%, [18][19][20][21] and data quality comparable to that collected by person-led phone interviews or IVR. 21 The cost of PREM administration has significant implications, yet receives little attention.…”
Section: Strengths and Limitations Of This Studymentioning
confidence: 97%
“…The content of the mobile features is tailored to specific populations, and the intervention may be delivered in conjunction with other therapies. mHealth interventions have been proven as evidence-based methods for concentrating on health treatments (Bock et al, 2015; Mason, Benotsch, Way, Kim, & Snipes, 2014) and have been used successfully for clinical assessment and education in medicine and public health (Christie, Dagfinrud, Dale, Schulz, & Hagen, 2014; Cooray, Matusevicius, Wahlgren, & Ahmed, 2015). Meta-analysis studies of mHealth clinical interventions for smoking cessation, weight loss, and diabetes control demonstrate these interventions are both cost effective and beneficial (Bakken et al, 2014; Gerber, Stolley, Thompson, Sharp, & Fitzgibbon, 2009; Pal et al, 2014; Riley, Obermayer, & Jean-Mary, 2008; Whittaker et al, 2012; Wieland et al, 2012).…”
mentioning
confidence: 99%
“…Patients with rheumatic diseases have expressed a need for frequent measurements of relevant outcomes, including patient‐reported outcomes that are extensively collected with pen‐and‐paper questionnaires. Christie et al described collection of patient‐reported outcomes in patients with inflammatory rheumatic disease via text messages on mobile telephones when compared with a pen‐and‐paper modality . Patient‐reported outcomes assessed using numeric rating scales and reported with text messages on mobile telephones or with pen‐and‐paper questionnaires provided comparable scores.…”
Section: Discussionmentioning
confidence: 99%
“…Patient‐reported outcomes assessed using numeric rating scales and reported with text messages on mobile telephones or with pen‐and‐paper questionnaires provided comparable scores. Furthermore, the text messages modality provided high response rates in a multicenter setting . Hawley et al compared paper records and electronic health records for completeness .…”
Section: Discussionmentioning
confidence: 99%